2009
DOI: 10.1097/brs.0b013e31819c3b61
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study of Clinical Outcomes in Patients With Cervical Compressive Myelopathy Treated With Open-Door or French-Door Laminoplasty

Abstract: Perioperative complications occurred more frequently in open-door laminoplasty than in French-door laminoplasty. JOA scores and recovery rates suggested that both open-door and French-door laminoplasties could be similarly effective in decompressing the spinal cord. Axial pain was improved in French-door laminoplasty but became worse in open-door laminoplasty. SF-36 suggested that French-door laminoplasty could be more beneficial than open-door laminoplasty for patients with cervical compressive myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 31 publications
1
81
1
1
Order By: Relevance
“…The relation between cervical mobility and axial pain has been noted [17,31], as the decrease in cervical lordosis or increase in cervical kyphosis would produce more axial pain. However, other studies [6,11,15,16,19,20] showed that postoperative axial pain did not correlate with postoperative cervical mobility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The relation between cervical mobility and axial pain has been noted [17,31], as the decrease in cervical lordosis or increase in cervical kyphosis would produce more axial pain. However, other studies [6,11,15,16,19,20] showed that postoperative axial pain did not correlate with postoperative cervical mobility.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement parameters were defined as cervical alignment (C2-7 Cobb angle), flexion-extension neck range of motion (ROM), anteroposterior diameter of the spinal canal (A-P canal diameter), preoperative instability, lamina closure and number of fused levels (Table 1). There were eight studies with the data on postoperative cervical alignment [6,31,47], changes in alignment [16], postoperative ROM [6,11,15,19,20] and changes in ROM [11,16]. The results showed that these factors were not correlated with postoperative axial pain in all these studies except one [31], in which minimal correlation between positive change of Cobb angle and improvement in axial pain was found.…”
Section: Radiological Assessmentmentioning
confidence: 98%
See 3 more Smart Citations